SOSIALISASI PENGEMBANGAN KEMAMPUAN LITERASI DIGITAL PADA SISWA SMAN 7 BEKASI - Putri, Martina Shalaty (Penerbit Widina, Widina Media Utama, 2024)
Digital literacy, particularly among children, has become an important topic that requires special attention. The Ministry of Communication and Information has developed a Digital Literacy curriculum consisting of four main pillars: Digital Skills, Digital Ethics, Digital Safety, and Digital Culture. SMAN 7 Bekasi, as a leading public high school in Bekasi, emphasizes the importance of digital literacy in shaping students who are competent and IT-savvy. Therefore, socialization of digital literacy development in the school is crucial. The socialization process involves presenting the importance of digital literacy development among students, both in terms of the positive and negative impacts of the internet, and how improving digital literacy skills is essential for the development of the younger generation in the digital era. Community service activities are carried out to enhance the understanding of SMAN 7 Bekasi students regarding digital literacy. By using persuasive and interactive communication methods and presenting relevant case studies, the activities have successfully increased students' understanding of digital literacy. However, the evaluation of the activities indicates that although most participants have a basic understanding of digital literacy, further improvement is needed to keep up with technology trends and developments.ABSTRAKLiterasi digital, khususnya di kalangan anak-anak, telah menjadi topik penting yang membutuhkan perhatian khusus. Kementrian Komunikasi dan Informasi mengembangkan kurikulum Literasi digital yang terdiri dari empat pilar utama: Keterampilan Digital, Etika Digital, Keamanan Digital, dan Budaya Digital. SMAN 7 Bekasi, sebagai SMA negeri unggulan di Bekasi, memiliki visi yang menekankan pentingnya literasi digital dalam pembentukan siswa yang unggul dan berwawasan IT. Oleh karena itu, sosialisasi pengembangan literasi digital di sekolah tersebut menjadi penting. Proses sosialisasi dilakukan dengan memaparkan pentingnya pengembangan literasi digital di kalangan siswa, baik dari dampak positif maupun negatif internet, serta bagaimana peningkatan kemampuan literasi digital menjadi penting bagi pengembangan generasi muda di era digital. Kegiatan pengabdian masyarakat dilakukan untuk meningkatkan pemahaman siswa SMAN 7 Bekasi tentang literasi digital. Dengan menggunakan metode komunikasi persuasif dan interaktif serta menyajikan contoh kasus yang relevan, kegiatan tersebut berhasil meningkatkan pemahaman siswa tentang literasi digital. Namun, evaluasi kegiatan menunjukkan bahwa meskipun sebagian besar peserta telah memiliki pemahaman dasar tentang literasi digital, diperlukan peningkatan lebih lanjut untuk mengikuti tren dan perkembangan teknologi.